The Effect of Human Resource Management Practices on Employees’ Motivation and Creativity in the Private Sector of Saudi Arabia - Al-Kazlah, Samerah Abdullah H.; Badkook, Roaa Osama (International Review of Management and Marketing, 2022)
By linking HRM practices with employees’ intrinsic motivation and creativity, we sought to evaluate the effectiveness of HRM practices for improving the enthusiasm and ingenuity of workers. More specifically, we investigated the impact of a package of HRM practices (i.e., job training and job design) on employees’ inherent motivation and the influence this has on their creativeness while performing their roles. Data were gathered from 416 employees in the private sector of Saudi Arabia to study how job training and design affected three basic determinants of intrinsic motivation—namely autonomy, relatedness, and competence—as well as the degree to which improvements in employee motivation have a positive effect on their creativity. The findings indicate that (1) overall job design has a positive and significant effect on employees’ motivation, with the most effective job design dimensions being task significance, feedback, and autonomy, while (2) job training also has a significant positive impact on intrinsic motivation. Moreover, (3) the results further demonstrate that (3) intrinsic job motivation has a significant effect in terms of encouraging employees to fulfil their roles in a more creative way.